2018
DOI: 10.1016/j.devcel.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Twist1 Activation in Muscle Progenitor Cells Causes Muscle Loss Akin to Cancer Cachexia

Abstract: Cancer cachexia is characterized by extreme skeletal muscle loss that results in high morbidity and mortality. The incidence of cachexia varies among tumor types, being lowest in sarcomas, whereas 90% of pancreatic ductal adenocarcinoma (PDAC) patients experience severe weight loss. How these tumors trigger muscle depletion is still unfolding. Serendipitously, we found that overexpression of Twist1 in mouse muscle progenitor cells, either constitutively during development or inducibly in adult animals, caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…In light of our present study, this discrepancy could be attributed to the genetic alterations in question, as TGIF1 seems to act mainly through repression of Twist1, whereas mutant p53 likely elicits its malignant effects through very complex mechanisms, often involving multiple genes and signaling pathways. It should be noted that our recent published studies have shown that pancreas‐specific deletion of Twist1 elicited either no effect or complete suppression of PDAC, depending on the genetic background (i.e., p16Ink4A deletion versus Trp53 deletion; Parajuli et al , ). These observations appear to reconcile all previously incongruent data regarding Twist1 in the context of PDAC and further shed important insights into the complex roles of this pro‐malignant transcription factor in PDAC, and perhaps in other human malignancies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In light of our present study, this discrepancy could be attributed to the genetic alterations in question, as TGIF1 seems to act mainly through repression of Twist1, whereas mutant p53 likely elicits its malignant effects through very complex mechanisms, often involving multiple genes and signaling pathways. It should be noted that our recent published studies have shown that pancreas‐specific deletion of Twist1 elicited either no effect or complete suppression of PDAC, depending on the genetic background (i.e., p16Ink4A deletion versus Trp53 deletion; Parajuli et al , ). These observations appear to reconcile all previously incongruent data regarding Twist1 in the context of PDAC and further shed important insights into the complex roles of this pro‐malignant transcription factor in PDAC, and perhaps in other human malignancies.…”
Section: Discussionmentioning
confidence: 94%
“…To generate the expression vector encoding Flag‐Twist1, Twist1 cDNA was obtained by PCR using pBABE‐puro‐mTwist1 as template and cloned into pBICEP‐CMV2‐3xFlag. To generate the p16 Luc reporter, genomic DNA (1,200 bp) upstream of the translation start site was amplified by the Genomic‐GC PCR amplification kit (BD Biosciences) using genomic DNA from HMLE cells as previously described (Parajuli et al , ). All cloned DNA fragments and their corresponding mutants were checked by sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, the GEM model KPC (Kras +/LSL−G12D , Trp53 +/R270H , Pdx1 +/Cre ) was reevaluated. Indeed, KPC is a GEM model of PDA (149) that has been recently considered a reliable model of cachexia by a number of studies [e.g., (11,150,151)]. Nonetheless, Talbert et al demonstrated that changes in size and tissue mass of KPC mice did not correlate with PDA progression, and that patterns of gene expression in their SM did not resemble that of PDA patients (144).…”
Section: Discrepancies: From the Laboratory To The Clinical Practicementioning
confidence: 99%
“…Previously, we used the ActRIIB-Fc ligand trap to demonstrate that catabolic TGF-β family myokines are necessary for castration-induced sarcopenia in tumor-free mice (16). The myokines that induce sarcopenia are primarily muscle derived, and catabolic signaling is paracrine from muscle stem (satellite) cells to myofibers (37), with only a minor endocrine contribution (38). In tumor-free mice, myostatin, activin A, and activin AB levels are increased in skeletal muscle 2 to 4 weeks after castration, prior to the onset of strength and muscle loss that occurs 6 weeks after castration (16).…”
Section: Discussionmentioning
confidence: 99%